2021
DOI: 10.3746/pnf.2021.26.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Beverage in Subjects with Metabolic Syndrome

Abstract: This study investigated the effects of fermented beverage, kale/apple juice containing 5% vinegar in subjects with metabolic syndrome. Subjects were randomly assigned to receive 250 mL fermented beverage or water containing fructose, glucose, and sucrose twice daily for 10 weeks. Consumption of the fermented beverage significantly decreased plasma triglyceride, thiobarbituric acid reactive substances (TBARS), tumor necrosis factor (TNF)-α, and high sensitivity C-reactive protein (hs-CRP) levels compared to bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Fermentation bulbs were indicated by blakish brown color, the odorius of onion, fermentation flavor (swetness and sour taste), soft layer's tuber and juicy. These characteristic were related to effect of maillard browning reaction [10]. The result was in aggreement with Louis Maillard [1912] who stated that Maillard's reaction is due to the amine acid reaction to sugar reduction which caused the changes of color and texture of foods.…”
Section: Fermented Onionmentioning
confidence: 68%
“…Fermentation bulbs were indicated by blakish brown color, the odorius of onion, fermentation flavor (swetness and sour taste), soft layer's tuber and juicy. These characteristic were related to effect of maillard browning reaction [10]. The result was in aggreement with Louis Maillard [1912] who stated that Maillard's reaction is due to the amine acid reaction to sugar reduction which caused the changes of color and texture of foods.…”
Section: Fermented Onionmentioning
confidence: 68%
“…On this basis, we can state that the amorphous character of hydroxyl propyl-modified cyclodextrins is enhanced by the interaction with the L35 copolymer as observed in flavonoids/HP-b-CD complexes. 47 We detected that the signal between 10 and 151 almost disappeared, indicating that the structure of the cyclodextrins was altered by the presence of L35. Similar observations are reported for the inclusion of PEG400 in the cavity of a-CD.…”
Section: Structural Properties Of L35/cd Polypseudorotaxanesmentioning
confidence: 86%
“…For example, the traditional Korean diet high in vegetables, seafood, and fermented foods is linked to better cognitive function and a reduced risk of cognitive impairment and dementia. [21,22] The identification of reliable biomarkers for pre-clinical MCI can facilitate disease prevention, prediction, monitoring, and treatment. Employing multi-omics analysis, which integrates data from various biological sources, previous studies have identified potential biomarkers for cognitive decline and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the traditional Korean diet high in vegetables, seafood, and fermented foods is linked to better cognitive function and a reduced risk of cognitive impairment and dementia. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%